Application of M-Factor in Seismic Assessment of An Existing MRT Building as per NBC 105:2020 and ASCE 41-17 - Phagu, Menaka; Rai, Sajan; Shrestha, Anup (Journal of Science and Engineering, 2026)
This study presents a comparative evaluation of seismic performance assessment methodologies for a Reinforced Concrete (RC) moment-resisting frame building originally designed using Mandatory Rules of Thumb (MRT) as per NBC 205:1994. The building is re-evaluated under the current prescriptive design framework of NBC 105:2020 and the advanced Performance-Based Design (PBD) methodology specified in ASCE 41-17, with particular emphasis on the role of the modification factor (m-factor) in seismic capacity evaluation. The objective is to examine the applicability, limitations, and effectiveness of conventional code-based design versus modern performance-oriented approaches in the context of existing buildings in seismically active regions. ASCE 41-17 provides a comprehensive and flexible framework grounded in nonlinear analysis and component-level performance objectives, enabling tailored seismic demand assessments under varying hazard scenarios. The study reveals significant discrepancies in structural performance, material utilization, safety margins, and retrofit implications between the two methodologies. The research advocates for the integration of performance-based assessment techniques, such as those in ASCE 41-17, to more accurately characterize seismic vulnerabilities and inform effective retrofit strategies. The findings support a shift toward more detailed and context-specific evaluation methods to enhance resilience and guide post-disaster reconstruction planning.